2005
DOI: 10.1007/s00383-005-1369-x
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal duplication cyst communicating with an aberrant pancreatic duct

Abstract: Duodenal duplication cyst (DDC) is an uncommon congenital anomaly and is the rarest site for intraabdominal duplications. We report a case of DDC communicating with an aberrant pancreatic duct in a 2-year-old girl, with features of possible occult relapsing pancreatitis. The duplication cyst was successfully enucleated with excision of the aberrant pancreatic duct. The literature is reviewed, and the diagnostic modalities and management options are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 13 publications
0
28
0
3
Order By: Relevance
“…A small population of such duplications is known to communicate with the pancreatic duct [2][3][4][5]. Holcomb et al [1] reported that 2 of 10 gastroduodenal duplications showed evidence of pancreatic tissue and ducts entering the duplication [2].…”
Section: Discussionmentioning
confidence: 99%
“…A small population of such duplications is known to communicate with the pancreatic duct [2][3][4][5]. Holcomb et al [1] reported that 2 of 10 gastroduodenal duplications showed evidence of pancreatic tissue and ducts entering the duplication [2].…”
Section: Discussionmentioning
confidence: 99%
“…Intrapancreatic variants of duodenal duplication cysts communicating with the main pancreatic duct have been described [7]. The spectrum of cystic lesions also includes intramural dilatations of the dorsal pancreatic duct (Santorinicele) [2]. Furthermore, different variants of choledochal cysts, which are a malformation of the intraduodenal part of biliaropan- creatic ducts, are reported in the literature [8][9][10].…”
Section: Discussionmentioning
confidence: 98%
“…Review of the literature about cystic lesions of the duodeno-biliaropancreatic region is complicated by the profusion of synonyms applied to these malformations [2]. Classical forms of duodenal duplication cysts are characterized by a location posteromedial to the second and third parts of the duodenum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…De acuerdo con su localización, se pueden clasificar en: duplicaciones del intestino delgado (íleo y yeyuno), que es el tipo más usual (47 %), de colon (20 %), de esófago (17 %), de estómago (8 %), de duodeno (2 a 12 %) y de otras localizaciones (1 a 5 %). Estos valores porcentuales varían según los diversos autores [12][13][14][15] . Duplicaciones esofágicas.…”
Section: Clasificaciónunclassified